PENERBITAN SERTIPIKAT HAK GUNA BANGUNAN No. 6226/KAMAL MUARA (PULAU D REKLAMASI) DIATAS HAK PENGELOLAAN No. 45/KAMAL MUARA OLEH KANTOR PERTANAHAN JAKARTA UTARA - Mohammad Agung Satria Rochmatulloh; Suparjo . (PALAR (Pakuan Law review), 2021)
Abstract Land registration is a series of activities conducted by the government on an ongoing basis and in an orderly manner which comprise the collection, processing, recording, presentation, and maintenance of physical and juridical data in the form of maps and registers concerning lands and apartments, including the issuance of right-evidencing documents for lands on which rights have been established as well as certain rights which encumbrances it. The implementation of land registration is become essential since such land registration aims to provide legal certainties and legal protection for the holder of rights over the land as well as to keep in operations orderly land administrative procedures. This writing uses a normative juridical method, namely research conducted to examine written legal norms which apply to analyze the issuance of Certificate of Rights to Build No. 6226/Kamal Muara over Rifhts to Management No. 45/Kamal Muara by North Jakarta Land Office with secondary data types and data collection tools for document studies or library materials. The result of this writing states whereby the issuing of certificate, which is part of land registration, in the form of Rights to Build No. 6226/Kamal Muara over Rights to Management No. 45/Kamal Muara with size of the land is 3.200.000 m2 registered as PT. K which located in Kelurahan Kamal Muara, Kecamatan Penjaringan, North Jakarta is meet with land procedures as well as applicable laws so that could make legal certainty on it and protection of public rights who will make use of such of a land. Keywords: Land, Certificate, Administration, Issuing, Registration, Right. Abstrak Pendaftaran tanah merupakan rangkaian kegiatan yang dilakukan pemerintah secara terus menerus, berkesinambungan dan teratur, yang meliputi pengumpulan, pengolahan, pembukuan, dan penyajian serta pemeliharaan data fisik dan data yuridis, dalam bentuk peta dan daftar, mengenai bidang-bidang tanah dan satuan-satuan rumah susun, termasuk pemberian surat tanda bukti haknya bagi bidang-bidang tanah yang sudah ada haknya serta hak-hak tertentu yang membebaninya. Pelaksanaan pendaftaran tanah menjadi penting karena pendaftaran tanah bertujuan memberikan kepastian hukum dan perlindungan hukum kepada pemegang hak atas suatu bidang tanah serta untuk terselenggaranya tertib administrasi pertanahan. Penelitian ini menggunakan metode yuridis normatif, yakni penelitian yang dilakukan untuk menelaah norma hukum tertulis yang berlaku untuk menganalisis penerbitan Sertipikat Hak Guna Bangunan 6226/Kamal Muara oleh Kantor Pertanahan Jakarta Utara dengan jenis data sekunder dan alat pengumpulan data studi dokumen atau bahan Pustaka. Hasil penelitian menyatakan bahwa penerbitan sertipikat, yang merupakan bagian dari pendaftaran tanah, berupa Hak Guna Bangunan No. 6226/Kamal Muara diatas Hak Pengelolaan No. 45/Kamal Muara dengan luas bidang tanah 3.200.000 m2 atas nama PT. K yang terletak di Kelurahan Kapuk Muara, Kecamatan Penjaringan, Kota Jakarta Utara telah memenuhi administrasi pertanahan serta ketentuan peraturan perundang-undangan yang berlaku sehingga dapat tercipta kepastian hukum dan perlindungan hak-hak (rights) masyarakat yang akan memanfaatkan area tanah tersebut.  Keywords: Administration, Certificate, Land, Reclamation, Registration, Rights.